2009
DOI: 10.2355/isijinternational.49.1372
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Synthesis and Characterization of TiC-reinforced Hadfield Manganese Austenitic Steel Matrix Composite

Abstract: An in-situ TiC-reinforced Hadfield manganese austenitic steel matrix composite has been synthesized by conventional melting and casting route. The microstructure has been characterized using an optical microscope, a scanning electron microscope coupled with an energy dispersive spectrometer and X-ray diffraction. Hardness and abrasion resistance have also been measured. The microstructure of the as-cast composite consists of austenite, a-ferrite and (Fe, Mn) 3 C together with TiC particles. The microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Prava Dalai et al [30] indicated that adding hard TiC particles into the austenitic manganese steel and secondary processing were beneficial for elastic modulus, hardness, and wear resistance. Srivastava and Das [31][32][33] demonstrated that austenite matrix with Ti(C,N) and (Ti,W)C precipitates could effectively protect the sliding surface. Huang et al [34] studied low alloy abrasion-resistant steel reinforced with self-generated TiC particles developed to improve its wear performance without increasing its hardness, and the results showed that the carbide precipitates were significantly helpful in resisting abrasive embedding and micro-cutting during abrasive wear.…”
Section: Introductionmentioning
confidence: 99%
“…Prava Dalai et al [30] indicated that adding hard TiC particles into the austenitic manganese steel and secondary processing were beneficial for elastic modulus, hardness, and wear resistance. Srivastava and Das [31][32][33] demonstrated that austenite matrix with Ti(C,N) and (Ti,W)C precipitates could effectively protect the sliding surface. Huang et al [34] studied low alloy abrasion-resistant steel reinforced with self-generated TiC particles developed to improve its wear performance without increasing its hardness, and the results showed that the carbide precipitates were significantly helpful in resisting abrasive embedding and micro-cutting during abrasive wear.…”
Section: Introductionmentioning
confidence: 99%